Realizing Ultrahigh Mechanical Flexibility and >15% Efficiency of Flexible Organic Solar Cells via a “Welding” Flexible Transparent Electrode - Chen, Xiaobin; Xu, Guiying; Zeng, Guang; Gu, Hongwei; Chen, Haiyang; Xu, Haitao; Yao, Huifeng; Li, Yaowen; Hou, Jianhui; Li, Yongfang (Advanced materials (Weinheim), 2020)
The power conversion efficiencies (PCEs) of flexible organic solar cells (OSCs) still lag behind those of rigid devices and their mechanical stability is unable to meet the needs of flexible electronics at present due to the lack of a high‐performance flexible transparent electrode (FTE). Here, a so‐called “welding” concept is proposed to design an FTE with tight binding of the upper electrode and the underlying substrate. The upper electrode consisting of solution‐processed Al‐doped ZnO (AZO) and silver nanowire (AgNW) network is well welded by utilizing the capillary force effect and secondary growth of AZO, leading to a reduction of the AgNWs junction site resistance. Meanwhile, the poly(ethylene terephthalate) is modified by embedding the AgNWs, which are then used to link with the AgNWs in the upper hybrid electrode, thus enhancing the adhesion of the electrode to the substrate. By this welding strategy, critical bottleneck issues relating to the FTEs in terms of optoelectronic and mechanical properties are comprehensively addressed. The single‐junction flexible OSCs based on this welded FTE show a high performance, achieving a record high PCE of 15.21%. In addition, the PCEs of the flexible OSCs are less influenced by the device area and display robust bending durability even under extreme test conditions. A “welding” transparent flexible electrode, with respect to both the upper electrode and the underlying substrate, for fabricating high‐performance flexible OSCs is proposed, resulting in a record power conversion efficiency of single‐junction flexible organic solar cells (OSCs) with excellent mechanical properties.